DEVELOPMENT PSICOMOTOR OF SCHOLARS WITH INDICATIVE OF ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) (Fiep Bulletin - online, 2014)
This paper had for objective to investigate the psicomotor development of scholls children with indicative of ADHD, with ages between 10 and 12 years. The study was characterized as descriptive. The sample was composed by 20 children with ages between 10 and 12 years, enrolled in a school of São José/SC. Two instruments were used: the protocol of DSM-IV, for the indication of ADHD and the Test for Evaluation of the Child's Movement (ABC). The statistical treatment was accomplished through descriptive statistics. Six children were classified with ADHD of the Combined Type, 11 with the Inattentive Type and 3 with the Type Hyperactive. With relationship to the scholars' motive abilities, it was observed that the girls had better permormance in the proofs of Manual Ability, was not significant while the boys obtained better results in the Balance and Abilities with Ball.  Ten children received the classification of Normal Motor Abilities, 5 received the classification Borderline Motor Disturbances and 5 Definitive Motor Problem. The difference among the classifications of ADHD was not significant, with relationship to the motor development. The presented results, when compared with other studies with normal populations, showed wich that children with ADHD are more sencibles to present psicomotor problems.
Keywords: Attention Deficit Hyperactivity Disorder (ADHD); Motor Development; Students